The Human Sausage Factory: A Study of Post-War Rumour in Tartu - Jeanmarie Rouhier-Willoughby (Journal of Ethnology and Folkloristics)
Book review of a monograph by Eda Kalmre, The Human Sausage Factory: A Study of Post-War Rumour in Tartu. Amsterdam: Rodopi, 2013. 180 p.